Systematic combing of Hemudu cultural symbols and analysis of modern value - Wang, Gaoshen; Jia, Weichen (Cultural Arts Research and Development, 2025)
This study presents a systematic investigation into the symbolic system of Hemudu culture, aiming to construct a comprehensive classification framework and explore the potential for modern reinterpretation and application. Drawing on an interdisciplinary methodology, we utilized bibliometric analysis via VOSviewer (v1.6.19), text mining with Python’s NLTK toolkit (v3.8.1), and field-based archaeological validation across six representative Hemudu sites. A total of 415 academic publications from CNKI, Web of Science, and JSTOR (2010–2023) were analyzed. Through this mixed-method approach, we identified three primary categories of cultural symbols: (1) production-related artifacts (e.g., bone ploughs, wooden paddles), (2) aesthetic and spiritual motifs (e.g., double-bird sunrise patterns, flame-shaped Jie carvings), and (3) architectural elements (e.g., dry-column stilt structures, mortise-and-tenon joints). Quantitative analysis indicates that approximately 78% of identified symbols serve dual functional and symbolic roles, with avian motifs exhibiting a semantic centrality of 0.89 in religious contexts. Based on our findings, we developed the first structured Hemudu Symbol Database (HSDv1.0) and proposed a dynamic lifecycle model for cultural symbol evolution, integrating Peircean semiotics with archaeological typology. This research contributes to the theoretical advancement of prehistoric cultural studies while providing practical pathways for cultural heritage preservation, such as digital database construction, AR-enhanced museum interpretation, and creative industry adaptation through technologies like Stratasys J850 Prime 3D printing. The study also demonstrates the value of cross-disciplinary integration among archaeology, semiotics, and digital humanities.